Características da marcha e oscilação postural no ortostatismo de crianças e adolescentes com paralisia cerebral: fatores biopsicossociais e efeito do kinesiotaping - Corsi, Carolina (2020)
According to the International Classification of Functionality, Disability and Health, functionality is the result of the interaction between the components of body structure and function, activity and participation, and contextual factors. The limitation of the activities of standing without support and walking have a relevant impact on the lives of children with cerebral palsy (CP), given their importance in promoting independence and allowing these children to explore the environment, directly impacting the social participation of this population. Considering the importance of identifying factors that may impact the functionality of children with CP, the first study was carried out, entitled "Biopsychosocial factors that influence the gait speed of children with cerebral palsy". This first study identified that factors such as sensory function, weekly hours of physical therapy and monthly family income interfere with gait speed. To identify the effect of physical therapy interventions on the gait of children with CP, a systematic review study was carried out entitled "Effect of physical therapy interventions on the spatio-temporal parameters of gait in children with cerebral palsy: a systematic review", which identified a positive effect of vibration platform training, gait training, transcranial stimulation and a negative effect of isolated muscle strengthening on gait speed. Kinesiotapingâ (KT) is a technique used in clinical practice in order to promote biomechanical alignment and muscle activation. However, the lack of evidence regarding its use during gait and the static balance of children with CP motivated studies three and four. Study 3 entitled “Effect of kinesiotapingâ on kinematics and muscle activation during gait in children with cerebral palsy” identified that placing taping on the middle gluteal and anterior tibial muscles of children with mild functional level CP increases gait speed, favors hip abduction and decreases muscle activity of the anterior tibialis, without significantly impairing the range of motion of the ankle, while the condition of the placebo KT seems to favor hip adduction and plantar flexion of the ankle during gait. Finally, the latest study entitled “Effect of kinesiotapingâ on the postural sway in the foot of children with cerebral palsy” showed that the placement of taping in the gluteus medius and anterior tibial muscles does not seem to have an immediate effect on the postural sway in standing children with CP at a light functional level, despite the trend found for greater postural oscillation in active and placebo conditions.